Pola ???7 Q1h ??? Penerapan Ujaran Al-Quran Pada Postingan Netizen +62 - Lia Dwi Utami (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
The increase in cases of hate speech, cyberbullying, and hoax news is an important concern. As a result, it can change the behavior of human civilization globally. As a Quranic solution, the 7Q1H pattern is hopeful in overcoming communication problems on social media. The purpose of this study is to what extent the negative effects of using technology and how to apply the 7Q1H pattern in anticipating the negative effects of using technology and social media. To explore, manage, and analyze data, in this study the researcher used the type of library research. From the results of this study the authors found that: (1) Inappropriate use of media can change the behavior of netizens. To date, 2,901 hoaxes have been recorded, 643 cases of hate speech have been recorded, and 84% of cyberbullying cases have been recorded on social media; and (2) The 7Q1H pattern is an utterance of the Koran as communication ethics in social media. 7Q1H consists of qaulan kariman (noble words), qaulan maysuran (light and pleasant words, qaulan balighan (fluent and memorable words), qaulan layyinan (soft words), qaulan sadidan (true words), qaulan ma'rufan (kind words), qaulan tsaqilan (words of value), and husnuzhan (good prejudice).